Morphometric Study of Anterior Clinoid Process and Optic Strut and the Ossification of Carotico-Clinoid Ligament with their Clinical Importance - Anne D Souza; Vrinda Hari Ankolekar; Nivedita Nayak; Mamatha Hosapatna; Antony Sylvan D Souza (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Knowledge about the ossification of the Carotico-Clinoid Foramen (CCF), as it forms a potential site for compression of the internal carotid artery may be beneficial for neurosurgeons and radiologists. Aim: To obtain a detailed knowledge of morphometry of Anterior Clinoid Process (ACP) and Optic Strot (OS) and the type of ossification of CCF which would be necessary to increase the success of surgeries related to the cavernous sinus and internal carotid artery. Materials and Methods: Parameters such as the length of ACP from its base to the tip, the width at its base and the distance between the tip of ACP to optic strut were measured in mm using digital calipers. SPSS version 17 was used for the statistical analysis. Paired t-test was applied to compare between right and left sides. Presence of carotico-clinoid foramen was observed and was classified as incomplete, contact form or complete. Results: The average length of ACP ranged from 12 to 15mm on right side and 11 to 16mm on the left side. Paired t-test was applied to compare the means between the right and left sides. The width of ACP varied between right and left sides and this difference was statistically significant (p<0.05). Out of 12 CCF observed, the commonest type was incomplete (N=7) followed by complete (N=3) and contact form (N=2). Conclusion: Considering the immense anatomical surgical and radiological importance of morphology of ACP, OS and CCF, this study highlighted the detailed morphometry of these structures. The study also has explained the sexual dimorphism in their morphology.